Establishing Appropriate Agency Relationships for Providers in China - Yu Liu MPH; Richard B. Saltman PhD (SAGE Publishing, 2019)
Physicians play multiple roles in a health system. They typically serve simultaneously as the agent for patients, for insurers, for their own medical practices, and for the hospital facilities where they practice. Theoretical and empirical results have demonstrated that financial relations among these different stakeholders can affect clinical outcomes as well as the efficiency and quality of care. What are the physicians' roles as the agents of Chinese patients? The marketization approach of China's economic reforms since 1978 has made hospitals and physicians profit-driven. Such profit-driven behavior and the financial tie between hospitals and physicians have in turn made physicians more the agents of hospitals rather than of their patients. While this commentary acknowledges physicians' ethics and their dedication to their patients, it argues that the current physician agency relation in China has created barriers to achieving some of the central goals of current provider-side health care reform efforts. In addition to eliminating existing perverse financial incentives for both hospitals and physicians, the need for which is already agreed upon by numerous scholars, we argue that the success of the ongoing Chinese public hospital reform and of overall health care reform also relies on establishing appropriate physician-hospital agency relations. This commentary proposes 2 essential steps to establish such physician-hospital agency relations: (1) minimize financial ties between senior physicians and tertiary-level public hospitals by establishing a separate reimbursement system for senior physicians, and (2) establishing a comprehensive physician professionalism system underwritten by the Chinese government, professional physician associations, and major health care facilities as well as by physician leadership representatives. Neither of these suggestions is addressed adequately in current health care reform activities.